2010
DOI: 10.1093/pch/15.7.419
|View full text |Cite
|
Sign up to set email alerts
|

Childhood overweight and obesity management: A national perspective of primary health care providers' views, practices, perceived barriers and needs

Abstract: Canadian primary health care providers are not adequately equipped to deal with the paediatric obesity epidemic. Effective assessment tools and treatment resources, dissemination of clinical practice guidelines, enhanced undergraduate medical education and postgraduate continuing medical education, and system-level changes are urgently needed to address this health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 17 publications
2
52
0
Order By: Relevance
“…9 Practitioners often rely on their professional judgment or on adult diagnostic criteria to identify pediatric obesity because they are unaware of, or lack access to, the appropriate diagnostic tools and guidelines. 12 There is evidence, however, that pediatricians who attended continuing medical education courses on obesity were more likely to use BMI-percentiles and had higher self-efficacy in practices related to childhood and adolescent overweight and obesity. 9,13 Systematic reviews have found strong evidence that childhood obesity prevention programs can reduce BMI, particularly those programs targeting children aged 6 to 12 years compared with those targeting teenagers.…”
mentioning
confidence: 99%
“…9 Practitioners often rely on their professional judgment or on adult diagnostic criteria to identify pediatric obesity because they are unaware of, or lack access to, the appropriate diagnostic tools and guidelines. 12 There is evidence, however, that pediatricians who attended continuing medical education courses on obesity were more likely to use BMI-percentiles and had higher self-efficacy in practices related to childhood and adolescent overweight and obesity. 9,13 Systematic reviews have found strong evidence that childhood obesity prevention programs can reduce BMI, particularly those programs targeting children aged 6 to 12 years compared with those targeting teenagers.…”
mentioning
confidence: 99%
“…Although not an exhaustive list of all interventions, to this end the following should be noted: awareness of the growing obesity crisis especially among young children (19), improvements in food labeling (20), the roll-out of a Diabetes Prevention Program (DPP)-based lifestyle intervention course (21), networking for common health purposes between industry, governments, obesity and activity researchers (17,18,22), efforts to value school-based physical activity (23) and of course, the venerable ParticipACTION campaign (24).…”
Section: Research Barriersmentioning
confidence: 99%
“…10 Obesity in school age is an escalating problem. 11 Typically, emotional or psychological problem is the first problem to face obese children, including low self-esteem. 12 Childhood obesity can be risk factor for many diseases such as: diabetes mellitus, hypertension, heart disease, sleep disorders, cancer, liver disease, eating disorders and asthma and other respiratory problems.…”
Section: Introductionmentioning
confidence: 99%